2021
DOI: 10.20944/preprints202102.0319.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated with Mortality Among Elderly People in the COVID-19 Pandemic (SARS-CoV-2): A Systematic Review and Meta-Analysis

Abstract: Keywords: SARS-CoV-2; COVID-19 ; Non Communicable diseases (NCDs). Clinical features; Institucionalized or hospitalized elderly; meta-analisys.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Pranata et al and Aliberti et al [33] also showed that higher clinical frailty scores were associated with higher mortality [16]. In other studies, factors associated with mortality include age; Charlson index; presence of diabetes, COPD, CKD, hypertension, or dementia; high d-dimer level; and high neutrophil-lymphocyte ratio [34][35][36].…”
Section: Et Al's Studymentioning
confidence: 94%
“…Pranata et al and Aliberti et al [33] also showed that higher clinical frailty scores were associated with higher mortality [16]. In other studies, factors associated with mortality include age; Charlson index; presence of diabetes, COPD, CKD, hypertension, or dementia; high d-dimer level; and high neutrophil-lymphocyte ratio [34][35][36].…”
Section: Et Al's Studymentioning
confidence: 94%